A chimeric protein of abrin and Abrus precatorius agglutinin that neutralizes abrin mediated lethality in mice. (1st March 2017) - Tiwari, Vinita; Bagaria, Shradha; Karande, Anjali A.
Abstract: Abrin, a type II ribosome inactivating protein from the Abrus precatorius plant, is extremely toxic. It has been shown to be 75 times more potent than its infamous sister toxin, ricin and their potential use in bio-warfare is a cause of major concern. Although several vaccine candidates are under clinical trials for ricin, none are available against abrin. The present study proposes a chimeric protein, comprising of 1–123 amino acids taken from the A chain of abrin and 124–175 amino acids from Abrus precatorius agglutinin A chain, as a vaccine candidate against abrin intoxication. The design was based on the inclusion of the immunogenic region of the full length protein and the minimal essential folding domains required for inducing neutralizing antibody response. The chimera also contains the epitope for the only two neutralizing antibodies; D6F10 and A7C4, reported against abrin till now. Active immunization with the chimera protected all the mice challenged with 45 X LD50 of abrin. Also, passive transfer of antibodies raised against the chimera rescued all mice challenged with 50 X LD50 of toxin. Hence the chimeric protein appears to be a promising vaccine candidate against abrin induced lethality. Highlights: A chimeric protein of A chain of Abrin and agglutinin was proposed as a vaccine against abrin. Vaccine design was based on inclusion of the immunogenic region of ABA and protective epitopes mAbs (D6F10 and A7C4). Chimera provided 100% protection up to 45 X LD50 abrin challenge in mice. Full protection was also seen up to 50 X LD50 abrin challenge in passive immunization studies.